Serum vitamin D3 levels are not associated with thyroid cancer prevalence in euthyroid subjects without autoimmune thyroid disease - Choi, Yun Mi (Korean J Intern Med, 2017)
BACKGROUND/AIMS: Previous studies have suggested that elevated serum vitamin D levels might protect against thyroid cancer. Elevated serum thyroid stimulating hormone levels and autoimmune thyroid disease (AITD) are suggested to be thyroid cancer promoting factors but have not been well controlled in previous studies. We designed the present study to evaluate whether serum vitamin D levels are associated with thyroid cancer in euthyroid patients with no clinical evidence of AITD. METHODS: This cross-sectional study included subjects who underwent routine health check-ups, including serum 25-hydroxy vitamin D3 (25(OH)D3) levels, anti-thyroid peroxidase antibody (TPO-Ab), and thyroid ultrasonography (US). Inclusion criteria were euthyroid, negative TPO-Ab, and no evidence of AITD by US findings. Thyroid cancer diagnoses were based on fine needle aspiration cytology and/or postsurgical histopathological findings. RESULTS: We enrolled 5,186 subjects (64% male, 37% female) in this study, including 53 patients (1%) with a diagnosis of thyroid cancer (33 males, 20 females). Mean 25(OH)D3 levels were similar between the thyroid cancer and control groups (p = 0.20). Subgroup analysis according to sex or seasonal variation also revealed no differences in 25(OH)D3 levels between the two groups. Based on the levels of 25(OH)D3, there was no significant difference in the prevalence of thyroid cancer; the prevalence was 0.71%, 0.94%, 1.40%, and 0.82% in the deficient, insufficient, sufficient, and excess groups, respectively (p = 0.64). CONCLUSIONS: The levels of serum 25(OH)D3 are not associated with thyroid cancer prevalence in euthyroid subjects with no clinical evidence of AITD.